Ecological assessment of ancological morbidity of the population of the Kulinsky region of Daghestan republic - A. G. Gasangadjieva; E. G. Abdurakhmanova; T. O. Ramazanova (Юг России: экология, развитие)
An ecological assessment of oncological morbidity of Kulinsky region population is given. There is investigated the consistence of heavy metals in soil, drinking water and flora. There’s revealed the arized concentrations of heavy metals in the soil and drinking water of the region.